2013
DOI: 10.1007/s11899-013-0162-5
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transplant Lymphoproliferative Disease (PTLD): Risk Factors, Diagnosis, and Current Treatment Strategies

Abstract: Post-transplant lymphoproliferative diseases (PTLD) are heterogeneous lymphoid disorders ranging from indolent polyclonal proliferations to aggressive lymphomas that complicate solid organ or hematopoietic transplantation. Risk factors have been identified, including viral infections, degree of immunosuppression, recipient age and race, allograft type, and host genetic variations. Clinically, extra-nodal disease is common, with 10–15 % presenting with central nervous system (CNS) disease. Most PTLD cases are B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
293
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(306 citation statements)
references
References 94 publications
(146 reference statements)
2
293
1
10
Order By: Relevance
“…Known CD20-negative variants of DLBCL include primary effusion lymphoma, plasmablastic lymphoma, anaplastic lymphoma kinasepositive DLBCL and large B-cell lymphoma arising in human herpes virus 8-associated multicentric Castleman disease [2,3]. Weak or negative CD20 levels have a significant negative impact on the survival of patients with DLBCL [4,5]. PEL, PBL and anaplastic lymphoma kinase-positive DLBCL are variably positive for CD30 [2].…”
Section: Discussionmentioning
confidence: 99%
“…Known CD20-negative variants of DLBCL include primary effusion lymphoma, plasmablastic lymphoma, anaplastic lymphoma kinasepositive DLBCL and large B-cell lymphoma arising in human herpes virus 8-associated multicentric Castleman disease [2,3]. Weak or negative CD20 levels have a significant negative impact on the survival of patients with DLBCL [4,5]. PEL, PBL and anaplastic lymphoma kinase-positive DLBCL are variably positive for CD30 [2].…”
Section: Discussionmentioning
confidence: 99%
“…Epstein-Barr virus-transformed B cells can proliferate without T-cell control in the face of immunosuppressive treatment after transplant. 4 Other infections, such as cytomegalovirus and hepatitis, have also been shown to increase the risk of PTLD. Further risk factors include treatment for acute rejection and heavy immuno suppressive burden, age, race, and genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Further risk factors include treatment for acute rejection and heavy immuno suppressive burden, age, race, and genetic factors. 4 The disease can affect the allograft and often can be extranodal involving the central nervous system, the gastrointestinal tract, and bone marrow; therefore, the clinical presentation of PTLD can vary depending on the organ affected. Lymphadenopathy is not always present but development of classic "B" sym ptoms should carry a high index of suspicion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the authors concluded that the present case was EBV non-associated lymphoma. In cases of EBV-related PTLD, the reduction of immunosuppression has been a mainstay of PTLD treatment (19). Rituximab, which is an anti-CD20 monoclonal antibody, is strongly suggested in a systemic disease (20).…”
Section: Case Reportmentioning
confidence: 99%